Analysis of Understanding Concept in Solving Mathematics Story problems Using CRI in Terms of Personality Types - N, AM. Hindi, Alfiah; S, HR, Iwan (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2020)
This research was aimed to determine the understanding concept of students in solving mathematics story problems CRI in terms of personality types. The research method was descriptive qualitative. Subjects in this research ware as many as 4 students, each 2 students with Extrovert personality types and 2 students with introverted personality types. Technique of Data collecting in this research using questionnaire instrument of personality type, about written story and interview. Based on the data analysis, the results of research indicate that: (1) the understanding concept of subject with extrovert personality type is at the level of ability of translation and interpretation. In solving the mathematical story problems, they are able to identify, present and apply the broad concept and circumference of the circle and provide a high CRI scale. Extrovert personality type shows that solving the subject matter is not careful, in a hurry as to dare to take risks from the work, done and to underestimate a thing, and to like the practical things. (2) the understanding concept of subject with introverted personality type is at the level of translation ability. In solving the mathematical story, they are only able to identify and present the concept of circles and provide a low CRI scale. According introverted personality type that shows in solving the subject matter are meticulous, careful, careful in solving the story problem, causing the subject with introverted personality type to be shy and not confident with the answers they write.